The Association Between Childcare Arrangement and Child Socioemotional Development - Seppälä, Milka (My University, 2021)
Toddlerhood is a time period of intensive and rapid social and emotional development, and this development is largely affected by the environment. The effects of different types of childcare arrangements on child socioemotionality have been widely studied, but the results have often been contradicting. Furthermore, only a handful of studies have addressed this issue in Finland. As the Finnish childcare system differs considerably from that of many other countries, it is important to study the associations between child socioemotional development and childcare type in the current Finnish context. The purpose of the present study was to compare the socioemotional development of two-year-old children who were either being cared for at home, or were participating in out-of-home, centre-based childcare. This study was conducted as a part of the larger FinnBrain Birth Cohort Study, and the sample (n = 1112) consists of those toddlers who were participating in one of these two types of childcare at the two-year age point, and whose mothers filled in the two-year survey. Socioemotional development was measured using the Brief Infant-Toddler Social and Emotional Assessment (BITSEA), a questionnaire that contains scales measuring internalising and externalising symptoms, dysregulation, and competence. Several background factors, such as parental education and income levels, were also considered. According to the results, toddlers who were in out-of-home, centre-based childcare displayed slightly more internalising symptoms than children who were in home care, after the effects of significant covariates were controlled. Internalising symptoms were also predicted by maternal education and paternal income level. No differences were found regarding externalising symptoms, social competence, or dysregulation. Furthermore, as the effect size of the final regression model was very small, the practical significance of the discovered difference in internalising remains unclear. Overall, the results of the present study offer preliminary support for the assumption that out-of-home, centre-based childcare and home care are not associated with remarkable differences in children’s socioemotionality. More research is needed in order to confirm this, and to investigate whether differences in the socioemotionality of children participating in different types of childcare develop in later childhood.

Taaperoikä on kiivaan sosioemotionaalisen kehityksen aikaa, ja lapsen elinympäristöllä on kehityksen etenemiseen suuri vaikutus. Useissa kansainvälisissä tutkimuksissa on tarkasteltu sitä, miten varhaiskasvatukseen osallistuminen vaikuttaa lapsen sosioemotionaaliseen kehitykseen, mutta tulokset ovat tähän mennessä olleet varsin ristiriitaisia. Suomessa aiheesta on tehty vain muutamia tutkimuksia. Suomalainen päivähoitojärjestelmä kuitenkin eroaa merkittävästi monien muiden maiden vastaavasta, joten olisi tärkeää tutkia hoitokontekstin yhteyttä lapsen sosioemotionaaliseen kehitykseen juurikin Suomessa. Tämän tutkimuksen tavoitteena oli verrata varhaiskasvatukseen osallistuvien ja kotihoidossa olevien kaksivuotiaiden lasten sosioemotionaalista kehitystä. Tutkimus toteutettiin osana laajempaa FinnBrain-syntymäkohorttitutkimusta. Tutkimusotos (n = 1112) koostuu niistä FinnBrain-kohortin lapsista, jotka olivat kaksivuotisikäpisteessä joko kotihoidossa tai päiväkodissa, ja joiden äiti täytti FinnBrain-tutkimuksen kaksivuotiskyselylomakkeen. Sosioemotionaalista kehitystä mitattiin tässä tutkimuksessa the Brief Infant-Toddler Social and Emotional Assessment -lomakkeella, joka sisältää internalisoivia ja eksternalisoivia oireita, säätelyvaikeuksia sekä sosiaalista kompetenssia mittaavat skaalat. Tutkimuksessa otettiin huomioon myös useita taustamuuttujia, kuten molempien vanhempien koulutus- ja tulotasot. Internalisoivia oireita esiintyi tässä tutkimuksessa päiväkodissa käyvillä lapsilla hiukan enemmän kuin kotihoidossa olevilla lapsilla. Äidin koulutustaso ja isän tuloluokka olivat myös yhteydessä lapsen internalisoiviin oireisiin, mutta hoitokontekstin yhteys internalisoiviin oireisiin säilyi merkitsevänä myös silloin, kun nämä taustamuuttujat kontrolloitiin. Eksternalisoivien oireiden, säätelyvaikeuksien ja sosiaalisen kompetenssin osalta eroja hoitomuotojen välillä ei löytynyt. On kuitenkin huomioitava, että päiväkodissa ja kotihoidossa olevien taaperoiden välinen ero internalisoivien oireiden suhteen oli erittäin pieni, samoin kuin syntyneen regressiomallin efektikoko, ja löytyneen eron käytännön merkitys on täten kyseenalainen. Tämän tutkimuksen tulosten perusteella vaikuttaisikin siltä, että varhaiskasvatukseen osallistuvien ja kotihoidossa olevien kaksivuotiaiden lasten sosioemotionaalisessa kehityksessä ei ole kovin suuria eroja. Tulevaisuudessa tarvitaan kuitenkin etenkin pitkittäisasetelmalla toteutettuja tutkimuksia, jotta asiasta voidaan saada varmempi käsitys.
Keywords: FinnBrain Birth Cohort Study, toddlerhood, socioemotional development, childcare, social competence, internalising symptoms, externalising symptoms, dysregulation